KAJI EKSPERIMENTAL PENGARUH VARIASI DIAMETER NOZZLE DAN DIAMETER RUNNER TERHADAP DAYA DAN EFISIENSI MODEL TURBIN PLETON - ., Supardi; Pramana, Chandra (MEKANIKA: Jurnal Teknik Mesin, 2015)
Pelton turbine is one type of impulse turbine, type of water turbine which works to change the available whole energy of water such as pressure, potential, and speed into kinetic energy to rotate turbines. Runner whichconsist of a number of blades is the main component on Pelton turbine when the turbine rotates because the force ofwater at high speed out of nozzle. Impulse reactions occur because the water jets hit the blades causing torque ofturbine shaft causing runner will continue rotates for object hit the blades. Experimental assessment was conductedto investigate effect of nozzle diameter variations as a media to transmit water and runner diameter variations asthe main media for generating mechanical energy in power and efficiency of the Pelton Turbine models in FluidLaboratorium August 17, 1945 University of Surabaya as a prototype model of Micro Hydro Power Plant( MHPP ). Stages of research was done by designing and planning some variation of the nozzle diameter and runnerdiameter with reference using head and flow capacity of available water pump. Specified parameters and variablesused for experimental assessment is single nozzle with diameter 0,006 m and 0,009 m and runner with diameter 0,15m, 0,17 m and 0,19 m. Blades used half cylinder shape with the specifications, width 0,036 m, length 0,027 m, depth0,00081 m, blade gap width 0,001 m, and the distance of center water emmision to blade tip 0,00135 m. From thetest results, variations of nozzle with diameter 0,006 m and runner with diameter 0,15 m produces the largestturbine power 49,53 watt, the best turbine efficiency of 87,97%, and the largest generator power 10,56 watt.Meanwhile, the variation nozzle with diameter of 0,009 m and runner with diameter 0,15 m, generating the bestgenerator efficiency 52.43%. From the characteristics graph of Pelton turbines, found same trend with the theorythat the efficiency of the turbine decreasing after reaching the maximum efficiency speed ratio of 0,46 and higherturbine efficiency directly proportional to turbine power produced.Keyword : Pelton Turbine, Nozzle, Runner, Power, Efficiency